The Effectiveness of Government Intervention: Indonesia Case - Nevi Danila; Eddy Suprihadi; Dwinita Ariyani (Journal of Accounting, Business and Management (JABM), 2011)
This paper observes the effectiveness of government intervention in Indonesia from market microstructure perspective, especially focusing on the dealers behavior in controlling their inventory by shifting the quotes since the dealers consider their optimal inventory every day, especially when there are events, for example government intervention, that might influence the value of their inventory. Thus, the paper will try to understand how intervention by Indonesia authorities in foreign exchange markets affected the quotation of foreign exchange rates, especially the setting of bid-ask prices. We found that dealers do not consider government intervention as a factor that influences them in controlling their inventory by shifting up and down the quotation. It seems that the intervention is not credible enough, in other words, the intervention is not effective.